Nitric oxide synthesis inhibition and anti-inflammatory effect of polypeptide isolated from chicken feather meal in lipopolysaccharide-stimulated RAW 264.7 macrophages - Inkanuwat, Aurachorn (Array, 2019)
Nitric oxide (NO) plays a key role in the pathogenesis of inflammation and has been implicated in endotoxin-induced tissue injury. Chicken feather meal is a rich source of amino acids that may serve as a peptide hydrolysate to inhibit NO activity. Anti-inflammatory hydrolysates of chicken feather meal were prepared and fractionated into five samples based on molecular mass.